2022
DOI: 10.32712/2446-4775.2022.1142
|View full text |Cite
|
Sign up to set email alerts
|

Evidências sobre a ação de compostos do Aloe vera em células cancerígenas: uma revisão da literatura

Abstract: A pesquisa tem como objetivo encontrar evidências científicas que apontem a ação anticancerígena dos compostos aloe-emodina e aloína em células neoplásicas. Este estudo consiste em uma revisão bibliográfica sobre o tema, de artigos publicados em revistas indexadas nas bases de dados online PubMed, Lilacs e SciELO, utilizando os descritores de forma combinada: “câncer”, “aloe-emodina” e “aloína”. As buscas foram realizadas em março de 2020, optando por artigos publicados nos últimos 5 anos, nos idiomas inglês e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…This study is consistent with [35] A. vera has traditionally been used to treat skin infections (burns, cuts, insect bites, eczema) and digestive problems due to its anti-inflammatory, antimicrobial, and wound-healing properties, the most active compounds responsible for these activities are aloin and aloe emodin, in addition to aloesin, emodin, and acemannan. This study also agrees with Borges & Hoefel [36] in vitro and in vivo studies revealed that compounds derived from A. vera (aloin-aloe emodin) had satisfactory results with regard to antitumor activity in different human cancer cell lines. Photodynamic therapy (PDT) mediated by aloin and aloe emodin shows potential for clinical development as an effective and safe new photosensitizer for the treatment of skin cancer [37].…”
Section: Detection Of Aloin Aloe Emodin Compounds In a Vera Leaves B...supporting
confidence: 91%
“…This study is consistent with [35] A. vera has traditionally been used to treat skin infections (burns, cuts, insect bites, eczema) and digestive problems due to its anti-inflammatory, antimicrobial, and wound-healing properties, the most active compounds responsible for these activities are aloin and aloe emodin, in addition to aloesin, emodin, and acemannan. This study also agrees with Borges & Hoefel [36] in vitro and in vivo studies revealed that compounds derived from A. vera (aloin-aloe emodin) had satisfactory results with regard to antitumor activity in different human cancer cell lines. Photodynamic therapy (PDT) mediated by aloin and aloe emodin shows potential for clinical development as an effective and safe new photosensitizer for the treatment of skin cancer [37].…”
Section: Detection Of Aloin Aloe Emodin Compounds In a Vera Leaves B...supporting
confidence: 91%